A New Approach to Predict Underground Gassiness for Design of Gas Capture and Ventilation Systems - Leszek W. Lunarzewski; Adam L. Lunarzewski; Raymond C. Pilcher (Society for Mining, Metallurgy & Exploration, 1995)
The Floorgas and Roofgas simulation programs are used to identify strata relaxation zones and their boundaries, to assess active gas sources from coal seams and gas¬bearing rocks and to determine relevant gassiness prediction coefficients for any local longwall. The paper shows that by use of the print-outs from the Floorgas and Roofgas programs the following benefits are achievable: • identification of the shear and gas discharge zone positions in the floor, strata relaxation angles and various gas discharge zone positions in the roof, which are both relevant to local geological and mining conditions • optimisation of cross-measure drainage hole length, location, number and angle of inclination calculation and definition of gas make prediction coefficients such as the release ratio from adjacent coal seams, specific gas emission during longwall extraction and the relationships between gas make, longwall width and coal production levels.